Dose-dependent effect of 2-deoxy-D-glucose on glycoprotein mannosylation in cancer cells - Ahadova, Aysel; Gebert, Johannes; Knebel Doeberitz, Magnus von; Kopitz, Jürgen; Kloor, Matthias (IUBMB life, 2015)
High glucose consumption due to Warburg effect is one of the metabolic hallmarks of cancer. Consequently, glucose antimetabolites, such as 2-deoxy-glucose (2DG), can induce substantial growth inhibition of cancer cells. However, the inhibition of metabolic pathways is not the sole effect of 2DG on cancer cells. As mannose-mimetic molecule, 2DG is believed to interfere with normal glycosylation of proteins in cells. Here, we address how 2DG influences protein glycosylation in cancer cells and discuss possible implications of the consequences of this influence. In detail, six colorectal cancer cell lines were examined for alterations of protein glycosylation by measuring monosaccharide incorporation into cellular glycoproteins and cell surface glycosylation by lectin FACS. A significant increase in mannose incorporation was observed on treatment with 2DG (1 mM for 48 h), which was also reflected by an increased binding of the mannose-binding lectin Concanavalin A in FACS analysis. This phenomenon, which could be reversed by external addition of mannose, was not caused by 2DG-mediated mannosidase inhibition, as shown by pulse-chase experiments, arguing in favor of the hypothesis that 2DG directly influenced the incorporation of mannose. Increased mannose content was generally observed in cellular glycoproteins, including glycoproteins isolated from the plasma membrane fraction. Our results indicate that 2DG at low doses, which have only a limited metabolism-related effect on glycosylation, induces a strong increase in mannose incorporation into cellular glycoproteins. On the other hand, higher 2DG concentrations (10 and 20 mM) led to a significant decrease of absolute mannose incorporation accompanied by a dramatically reduced protein synthesis rate. 2DG-induced alterations of glycosylation may represent a novel mechanism potentially explaining the varied effects of 2DG on cancer cells. Moreover, 2DG treatment may open a path toward novel diagnostic and cancer therapeutic approaches, which specifically target altered glycoantigen structures induced by 2DG. © 2015 IUBMB Life, 67(3):218-226, 2015